Extent of wild–to–crop interspecific introgression in grapevine (Vitis vinifera) as a consequence of resistance breeding and implications for the crop species definition. Issue 1 (31st January 2022) - Foria, Serena; Magris, Gabriele; Jurman, Irena; Schwope, Rachel; De Candido, Massimo; De Luca, Elisa; Ivanišević, Dragoslav; Morgante, Michele; Di Gaspero, Gabriele
Abstract: Over the past two centuries, introgression through repeated backcrossing has introduced disease resistance from wild grape species into the domesticated lineage Vitis vinifera subsp. sativa . Introgression lines are being cultivated over increasing vineyard surface areas, as their wines now rival in quality those obtained from preexisting varieties. There is, however, a lot of debate about whether and how wine laws defining commercial product categories, which are based on the classification of V. vinifera and interspecific hybrid grapes, should be revised to accommodate novel varieties that do not fit either category. Here, we developed a method of multilocus genotype analysis using short–read resequencing to identify haplotypic blocks of wild ancestry in introgression lines and quantify the physical length of chromosome segments free–of–introgression or with monoallelic and biallelic introgression. We used this genomic data to characterize species, hybrids and introgression lines and show that newly released resistant varieties contain 76.5–94.8% of V. vinifera DNA. We found that varietal wine ratings are not always commensurate with the percentage of V. vinifera ancestry and linkage drag of wild alleles around known resistance genes persists over at least 7.1–11.5 Mb, slowing down the recovery of the recurrent parental genome. This method also allowed us to identify the donor species of resistance haplotypes, define the ancestry of wild genetic background in introgression lines with complex pedigrees, validate the ancestry of the historic varieties Concord and Norton, and unravel sample curation errors in public databases.